Respuesta :

Answer:

x = (c+a)/2

y = (c-a)/2

Step-by-step explanation:

Add the two equations and you get ...

(x +y) +(x -y) = (c) +(a)

2x = c+a

x = (c+a)/2

--

Subtract the second equation from the first and you get ...

(x +y) -(x -y) = (c) -(a)

2y = c-a

y = (c-a)/2

_____

Comment on this problem

This is what I call a "sum and difference" problem. The solution shown here is (obviously) the generic solution to such a problem. Remembering this can get you quickly to the answer any time you're given the sum of two unknowns and their difference.

ACCESS MORE